A Bioinspired Fair Resource-Allocation Algorithm for TDMA-Based Distributed Sensor Networks for IoT. (11th April 2016) - Kim, Young-Jae; Choi, Hyun-Ho; Lee, Jung-Ryun
Abstract : Many studies on distributed resource-allocation algorithms have been conducted recently because of the increasing number of network nodes and the rapidly changing network environments in the Internet of Things (IoT). In this paper, we propose the multihop DESYNC algorithm, which is a bioinspired Time Division Multiple Access- (TDMA-) based distributed resource-allocation scheme for distributed sensor networks. We define a detailed frame structure for the proposed multihop DESYNC algorithm and a firing message, which acts as a reference for resource allocation. In addition, operating procedures for resource allocation and collision detection avoidance under multihop DESYNC are explained. Simulations show that multihop DESYNC effectively resolves the hidden-node problem and that it fairly shares resources among nearby nodes in multihop networks. Moreover, it achieves better performance than the CSMA/CA algorithm in terms of channel reuse gain and average throughput.